2017
DOI: 10.1002/slct.201701188
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Component Cascade Reaction in a Tube: In Situ Synthesis of Pd Nanoparticles Supported on mpg‐C3N4, Dehydrogenation of Ammonia Borane and Hydrogenation of Nitroarenes

Abstract: We report herein a facile in situ synthesis of Pd nanoparticles (NPs) supported on mesoporous graphitic carbon nitride (mpg-C 3 N 4 /Pd) during the tandem dehydrogenation of ammonia borane (AB) and hydrogenation of nitroarenes at room temperature. In the presented protocol, a three-component cascade reaction is realized in a pressure tube at room temperature, encompassing (i) in situ generation of Pd NPs supported on mpg-C 3 N 4 via reduction of mpg-C 3 N 4 /Pd(II) nanocomposites by AB, (ii) the mpg-C 3 N 4 /P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Based on our earlier attempts at hydrogenation and reductive amination, [20][21][22][23][24][25] we tried to optimize the hydrogenation conditions by experimenting with different parameters, such as solvent, temperature, time, the catalyst, and the amount of AB. 4′-Methoxyacetophenone was selected as the model reagent for the synthesis of the corresponding alcohol under optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our earlier attempts at hydrogenation and reductive amination, [20][21][22][23][24][25] we tried to optimize the hydrogenation conditions by experimenting with different parameters, such as solvent, temperature, time, the catalyst, and the amount of AB. 4′-Methoxyacetophenone was selected as the model reagent for the synthesis of the corresponding alcohol under optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…22 In a recent study, we have also demonstrated that in situ synthesized Pd NPs supported on mesoporous graphitic carbon nitride (mpg-C 3 N 4 /Pd) are highly efficient catalysts in the A facile and highly efficient transfer hydrogenation of ketones and aldehydes catalyzed by palladium nanoparticles supported on mesoporous graphitic carbon nitride TH of nitroarenes to the corresponding aniline derivatives at room temperature. 23 In order to clarify the efficiency of the newly developed mpg-C 3 N 4 /Pd catalyst, we describe herein an efficient, selective, and fast reduction chemistry method for the synthesis of alcohols using AB as a hydrogen source with mpg-C 3 N 4 /Pd in a water/methanol mixture (v/v = 1/1). In addition, it should be noted that less AB was used for the hydrogenation reactions compared to our previous studies, [20][21][22][23] making our new methodology cost efficient and more practical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, upon the results of our research direction, addressed herein is the performance of binary Cu 7 Pt 3 alloy NPs assembled on reduced graphene oxide (Cu 7 Pt 3 ‐rGO) as catalyst for the TH using AB as a hydrogen donor molecule and water as sole solvent performed in a commercially available high‐pressure glass tube at room temperature. It should be noted that this study differs from our previous studies not only using CuPt‐rGO as the catalyst but also utilization of water as the sole solvent instead of aqueous methanol solution, which is considered to be important in terms of green chemistry …”
Section: Introductionmentioning
confidence: 93%
“…Palladium (Pd)-based catalysts have been previously demonstrated to be active materials for dehydrogenation of NH 3 BH 3 and selective hydrogenation of nitroarenes to anilines. Although Pd nanoparticles (NPs) feature outstanding catalytic activity for the useful reactions, they are apt to aggregate, thus limiting their wide usages. To overcome this issue, the restriction of Pd NPs inside porous materials is known to be an effective method. …”
Section: Introductionmentioning
confidence: 99%